2009
DOI: 10.1007/s00192-009-0825-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental biomechanical evaluation of polypropylene prostheses used in pelvic organ prolapse surgery

Abstract: When the biomechanical parameters were comparatively assessed, HWPP was considered to have the most advantageous properties for prolapse surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…After implantation, all materials will be subjected to cell interactions with the scaffolds and it has been suggested that PPL contracts by~15% after implantation [32,33]. Accordingly, we examined the extent of intrinsic contraction of the scaffolds both without and with cells and found that PLA and SIS both contracted by~15%.…”
Section: Discussionmentioning
confidence: 96%
“…After implantation, all materials will be subjected to cell interactions with the scaffolds and it has been suggested that PPL contracts by~15% after implantation [32,33]. Accordingly, we examined the extent of intrinsic contraction of the scaffolds both without and with cells and found that PLA and SIS both contracted by~15%.…”
Section: Discussionmentioning
confidence: 96%
“…Mesh shrinkage has been reported to occur early after tissue implantation, within the first 14 days of tissue healing in response to the acute inflammatory reaction [19]. After this early phase, mesh shrinkage defined as surface loss measured in millimeters and expressed as a percentage of initial surface area, and which occurs in 72% of all implants, was stable over a 180-day period in a rabbit abdominal model where it correspond to 3-20% of the initial surface area [19].…”
Section: Discussionmentioning
confidence: 99%
“…After this early phase, mesh shrinkage defined as surface loss measured in millimeters and expressed as a percentage of initial surface area, and which occurs in 72% of all implants, was stable over a 180-day period in a rabbit abdominal model where it correspond to 3-20% of the initial surface area [19].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in the biomechanical properties of implants because they might be crucial for anatomical as well as functional outcome following sling surgeries for incontinence and mesh‐augmented prolapse repair 1 . Experimental studies investigating the deformation behaviour of materials both before and after implantation may contribute to a more evidence‐based choice of materials used clinically 2–6 . Outcome measures of such experiments include stress (or force), strain (or displacement), their relationship or compliance , and maximal force at disruption.…”
Section: Introductionmentioning
confidence: 99%
“…1 Experimental studies investigating the deformation behaviour of materials both before and after implantation may contribute to a more evidence-based choice of materials used clinically. [2][3][4][5][6] Outcome measures of such experiments include stress (or force), strain (or displacement), their relationship or compliance, and maximal force at disrup-tion. The focus in current implant design is on developing materials that are less stiff.…”
Section: Introductionmentioning
confidence: 99%